Reduction of Postoperative Wound Infections by Antiseptica (RECIPE)?: A Randomized Controlled Trial. Issue 1 (July 2020) - Strobel, Rahel M.; Leonhardt, Marja; Krochmann, Anika; Neumann, Konrad; Speichinger, Fiona; Hartmann, Lisa; Lee, Lucas D.; Beyer, Katharina; Daum, Severin; Kreis, Martin E.; Lauscher, Johannes C.
Abstract : Objective: To evaluate whether intraoperative subcutaneous wound irrigation with 0.04% polyhexanide can reduce surgical site infection (SSI) in elective laparotomies compared to saline. Background: SSI is a common complication after gastrointestinal surgery. To date, there is a lack of evidence whether subcutaneous wound irrigation is beneficial in terms of reduction of SSI. Methods: The RECIPE trial was an investigator initiated single-center, single-blind prospective, randomized controlled trial with 2 parallel treatment groups, comparing wound irrigation with 0.9% saline to antiseptic 0.04% polyhexanide solution in elective laparotomies. Primary endpoint was the rate of SSI within 30 days postoperatively according to Centers for Disease Control and Prevention criteria. Results: Between February 02, 2015, and May 23, 2018, 456 patients were randomly assigned to saline (n = 228) or polyhexanide (n = 228). Final cohort for analysis comprised 393 patients (202 in the saline and 191 in the polyhexanide group). Overall rate of SSI was 28.2%, n = 111. Simple analysis with cross tabulation revealed that significantly fewer SSIs occurred in the polyhexanide group: n = 70 (34.7%) versus n = 41 (21.5%); P = 0.004. In a multiple logistic regression model the factor wound irrigation with polyhexanide [odds ratio (OR) 0.44; 95% confidence interval (CI) 0.27–0.72; P = 0.001) was associated with risk reduction of SSI. Preoperative anemia (OR 2.08; 95% CI 1.27–3.40; P = 0.004) and more than 5 prior abdominal operations compared to none (OR 8.51; 95% CI 2.57–28.21; P < 0.001) were associated with SSI. Conclusions: Intraoperative subcutaneous wound irrigation with antiseptic 0.04% polyhexanide solution is effective in reducing SSI after elective laparotomies.